The Influence Of Transformational And Transactional Leadership Styles On Knowledge Sharing And Employees Performance In Condong Catur Hospital - Eko Winingsih, Apriyani (Riviera Publishing, 2022)
The purpose of this research is to empirically study transformational and transactional leadership styles on knowledge sharing and performance. The research design uses a quantitative approach through research instruments. The unit of analysis in this study were employees of the Condong Catur Hospital. Data was collected via google form by HRD RSCC. Saturation sampling was used to collect the sample of this study. The total respondents in this study were 147 people who were employees of the Condong Catur Hospital. This study shows that the transformational leadership style has a positive and significant effect on knowledge sharing. This empirical finding also shows the positive and significant effect of transactional leadership style on knowledge sharing, transformational leadership style on performance, transactional leadership style on performance and knowledge sharing on performance